Inside Back Cover: The Miharamycins and Amipurimycin: their Structural Revision and the Total Synthesis of the Latter (Angew. Chem. Int. Ed. 31/2019). Issue 31 (5th July 2019) - Wang, Shengyang; Zhang, Qingju; Zhao, Yachen; Sun, Jiansong; Kang, Wenjia; Wang, Fei; Pan, Haixue; Tang, Gongli; Yu, Biao
Abstract : The structures of Amipurimycin and the Miharamycins are described by B. Yu and co‐workers in their Communication on page 10558 ff. These natural products were discovered over 40 years ago and eight diastereoisomers have been synthesized in the search for the correct structure. This journey is represented by a zigzag bridge with nine turns leading to a pavilion in an oriental garden.